Forced Migration and Global Responsibility for Health; Comment on "Defining and Acting on Global Health: The Case of Japan and the Refugee Crisis" - Kayvan Bozorgmehr; Oliver Razum (Kerman University of Medical Sciences, 2017)
Forced migration has become a world-wide phenomenon in the past century, affecting increasing numbers of countries and people. It entails important challenges from a global health perspective. Leppold et al have critically discussed the Japanese interpretation of global responsibility for health in the context of forced migration. This commentary complements their analysis by outlining three priority areas of global health responsibility for European Union (EU) countries. We highlight important stages of the migration phases related to forced migration and propose three arguments. First, the chronic neglect of the large number of internally displaced persons (IDPs) in the discourses on the "refugee crisis" needs to be corrected in order to develop sustainable solutions with a framework of the Sustainable Development Goals (SDGs). Second, protection gaps in the global system of protection need to be effectively closed to resolve conflicts with border management and normative global health frameworks. Third, effective policies need to be developed and implemented to meet the health and humanitarian needs of forced migrants; at the same time, the solidarity crisis within the EU needs to be overcome. These stakes are high. EU countries, being committed to global health, should urgently address these areas.